2019
DOI: 10.3390/land8010006
|View full text |Cite
|
Sign up to set email alerts
|

Can Multifunctional Landscapes Become Effective Conservation Strategies? Challenges and Opportunities From a Mexican Case Study

Abstract: Protected Areas (PA) are the main strategy for nature conservation. However, PA are not always efficient for ecological conservation and social wellbeing. A possible alternative for conservation in human-dominated landscapes are Multifunctional Landscapes (ML), which allow the coexistence of multiple objectives, such as nature conservation and resource use. Using the activity system framework, we analyzed whether the ML concept was an operative alternative to PA within an area of interest for conservation in V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
6
0
2
Order By: Relevance
“…One case reported on a failing attempt to establishing a protected area and difficulties with achieving common agreements and objectives between stakeholders in the area. Some stakeholders focused on conserving the area, but most stakeholders did not have conservation of the landscape as a main goal [50]. Consensus building between stakeholders was thus challenging and power inequalities posed difficulties [49].…”
Section: Interaction Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…One case reported on a failing attempt to establishing a protected area and difficulties with achieving common agreements and objectives between stakeholders in the area. Some stakeholders focused on conserving the area, but most stakeholders did not have conservation of the landscape as a main goal [50]. Consensus building between stakeholders was thus challenging and power inequalities posed difficulties [49].…”
Section: Interaction Problemsmentioning
confidence: 99%
“…In the planning and visioning process, a lack of landscape institutions in place posed problems to negotiation [43,50,57]. As Ros-Cuéllar et al [50] and Chia and Sufo [58] reported, a lack of multi-sectoral platforms hindered information sharing among stakeholders, and this hampered the development of collaborative strategies for adaptive management. Moreover, sectorial planning traditions [47,59] and governance complexity presented challenges [52].…”
Section: Institutional Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…One is that less than 13% of the Earth's surface is protected in natural reserves (Groom et al, 2006), so that many species have to survive in managed landscapes (Winfree et al, 2007). Conserving biodiversity in agricultural landscapes is therefore an increasing priority, especially considering the important ecosystem services it provides (e.g., Clough et al, 2011; Mastrangelo & Gavin, 2012; Ros‐Cuéllar et al, 2019; Tscharntke et al 2005). Some managed areas can support more species than was previously thought (Winfree et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several interactions are established between social and ecological processes in landscapes occupied by agriculture, and there are many challenges, considering food production in a fair and equitable way, food security, conservation of agrobiodiversity and the obtaining of social and cultural benefits. A possible alternative is to build landscapes that allow multiple objectives to coexist, such as nature conservation and the use of resources (Ros-Cuéllar, Porter-Bolland & Bonilla-Moheno, 2019), increasing ecological functionality while bringing benefits to human well-being (Bowman et al, 2017). This new perspective involves dialoguing with local communities, promoting social participation and valorization of local and traditional knowledge, besides the development of agroecological practices (Oliveira & Morais, 2019).…”
Section: Introductionmentioning
confidence: 99%